Desenvolvimento de um novo peptídeo com atividade antimicrobiana (bactérias e leveduras) e antiproliferativa em células neoplásicas: análises in silico, in vitro e in vivo - LUÍS HENRIQUE DE OLIVEIRA ALMEIDA (2023)
Antimicrobial resistance (AMR) acquired by microorganisms, whether naturally or due to the indiscriminate use of antimicrobials, and multidrug resistance (MRD) acquired by microorganisms and also by cancer cells, has become a serious public health problem throughout the world. world. Microorganisms, in addition to being able to overcome the effects of antimicrobials, also present biofilm formation as a form of resistance, which makes the treatment of microbial infections even more difficult. This highlights the importance of discovering and/or developing new antimicrobial and anticancer agents. Among the classes of biomolecules, peptides have stood out due to their broad spectrum of biological activities. With this in mind, in this study a new antimicrobial peptide (AMP) was developed, based on a peptide encrypted in the sequence of Inga laurina seed trypsin inhibitor (ILTI). To obtain the AMP, the ILTI sequence was fragmented in silico, obtaining 169 fragments, and the fragment that presented the greatest antimicrobial potential was chosen for study. Changes in the positioning of amino acid residues and exchange of amino acid residues in the selected sequence were carried out, thus obtaining a AMP with 19 amino acid residues called KWI-19. In silico evaluations of the physicochemical characteristics of the peptide sequence obtained showed desirable parameters for a AMP. Once this was done, homology modeling was carried out, the validation of the lower energy model (more stable) and subsequently the synthesis of the peptide using solid phase methodology (SPSP), followed by its purification by high performance liquid chromatography (HPLC) and determination of its mass by mass spectrometry using the technique matrix assisted laser desorption/ionization time-of-flight (MALDI-TOF). The evaluation of the cytotoxicity of the peptide in vitro and in vivo was carried out and it was found that the peptide presented a hemolytic concentration in 50% of erythrocytes at a concentration of 6.54 μmol L-1. Regarding the in vivo acute toxicity test on Galleria mellonella larvae, no toxic effects were observed. In vitro tests were carried out with Gram-positive and negative bacteria, and with yeasts belonging to the Candida genus. KWI-19 inhibited bacterial growth with minimum inhibitory and bactericidal concentrations (MIC and MBC) ranging from 1.25 to 10 μmol L-1. Of the yeast species tested, KWI-19 inhibited growth at minimum inhibitory and fungicidal concentrations (MIC and CFM) ranging from 2.5 to 20 μmol L-1. Due to the results obtained, the species of Pseudomonas aeruginosa, Staphylococcus saprophyticus and C. tropicalis were chosen for further studies. For these species, we carried out death kinetic assays, where it was found that KWI-19 inhibits bacterial and fungal growth, in MBC and MFC, from 30 min for S. saprophyticus, in 120 minutes for P. aeruginosa and in 60 min for C. tropicalis. Assays to determine the peptide's mode of action were carried out, and in the nucleic acid release assay, in bacteria, it was observed that there is a greater amount of DNA and RNA present in the extracellular environment, when the strains were treated with KWI-19 . In the crystal violet uptake assay, it was not possible to observe a statistical difference between bacteria treated and not treated with KWI-19. To investigate the mode of action of KWI-19 in yeast, assays were carried out using the SYTOXTM Green probe and another using ergosterol and sorbitol. In these assays it can be seen that KWI-19 acts on the yeast plasma membrane. The effects of KWI-19 on inhibiting biofilm formation and eradicating mature biofilm from selected strains were also evaluated and biofilm viability was quantified with the total number of viable colony forming units (CFU), where KWI-19 inhibited and eradicated part of the biofilm from all study strains. Cell viability assays with the murine melanoma line B16F10-Nex2 were performed and the peptide showed an IC50 of 22.1 μmol L-1, where it was verified, by flow cytometry, that the main cell death process activated by KWI-19 is necrosis. Keywords: encrypted peptide, antibacterial, antifungal, antibiofilm, anticancer.